Implementation Of Seabank Digital Banking Technology And Its Impact On Community Economic Empowerment In Dumai City - Prabowo, Edy; Agnes, Agnes; Irawan, Metha Angelina; Wulandari, Putri; Sheltya, Sheltya; Laia, Yolanda Putri Anastashya (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the implementation of SeaBank's digital banking technology and its impact on community economic empowerment in Dumai City using a descriptive qualitative approach. Research data were obtained through in-depth interviews with SeaBank customers, observation of application usage, and analysis of documentation from SeaBank's 2024 annual report and various related journals. The results of the study show that SeaBank has succeeded in increasing financial inclusion in Dumai City through innovative features such as digital account opening, daily savings interest, and transactions without administration fees, thus facilitating access to financial services for the community and MSMEs. The significant increase in the number of customers, transaction volume, and credit distribution during 2024 proves the effectiveness of SeaBank's digital transformation in driving local economic growth. However, challenges such as low financial literacy and limited digital infrastructure are still major obstacles that need to be overcome so that the benefits of digital banking can be felt evenly. This study recommends increasing financial literacy education, developing digital infrastructure, and strengthening collaboration between SeaBank, the government, and other stakeholders to support sustainable community economic empowerment in Dumai City.